Introduction to analytical mechanics - Gamalath, K. A. I. L. W. (Alpha Science International, 2011)
Offers a modern treatment of classical mechanics so that transition to many fields in physics can be made with the least difficulty. This book deals with the formulation of Newtonian mechanics, Lagrangian dynamics, which are formulating the quantum mechanics and Hamilton-Jacobi equation which provides the transition to wave mechanics